Dpp4+ interstitial progenitor cells contribute to basal and high fat diet-induced adipogenesis - Megan Stefkovich; Sarah Traynor; Lan Cheng; David Merrick; Patrick Seale (Elsevier, 2021)
Objective: The capacity to generate new adipocytes from precursor cells is critical for maintaining metabolic health. Adipocyte precursor cells (APCs) constitute a heterogenous collection of cell types; however, the contribution of these various cell types to adipose tissue expansion in vivo remains unknown. The aim of the current study is to investigate the contribution of Dpp4+ progenitors to de novo adipogenesis. Methods: Single cell analysis has identified several transcriptionally distinct subpopulations of APCs, including Dpp4+ progenitor cells concentrated in the connective tissue surrounding many organs, including white adipose tissue (WAT). Here, we generated a Dpp4CreER mouse model for in vivo lineage tracing of these cells and their downstream progeny in the setting of basal or high fat diet (HFD)-stimulated adipogenesis. Results: Dpp4CreER mice enabled specific temporal labeling of Dpp4+ progenitor cells within their native connective tissue niche. Following a dietary chase period consisting of chow or HFD feeding for 18 weeks, Dpp4+ progenitors differentiated into mature adipocytes within the gonadal and subcutaneous WAT. HFD stimulated adipogenic contribution from Dpp4+ cells in the gonadal but not the subcutaneous depot. Flow cytometry analysis revealed that Dpp4+ progenitors give rise to DPP4(−)/ICAM1+ preadipocytes in vivo. HFD feeding did not perturb the flux of Dpp4+ cell conversion into ICAM1+ preadipocytes in gonadal WAT. Conversely, in subcutaneous WAT, HFD feeding/obesity led to an accumulation of ICAM1+ preadipocytes without a corresponding increase in mature adipocyte differentiation. Examination of non-classical murine visceral depots with relevance to humans, including omentum and retroperitoneal WAT, revealed robust contribution of Dpp4+ progenitors to de novo adipogenesis, which was further stimulated by HFD. Conclusion: Our data demonstrate that Dpp4+ interstitial progenitor cells contribute to basal adipogenesis in all fat depots and are recruited to support de novo adipogenic expansion of visceral WAT in the setting of HFD-induced obesity.